Empowering Youth: The Role of Reproductive Health Education in Mitigating Adolescent Misbehavior - Sulastri Sulastri; Sri Nurhayati (Pusdikra-Publishing.com, 2023)
This research aims to analyze: (1) planning; (2) implementation; and (3) the results of Reproductive Health Counseling to Reduce Adolescent Delinquency Cases in Srikamulyan Village. The method used is qualitative, with research subjects consisting of adolescents, counselors, and the government of Srikamulyan Village. The research location is in Srikamulyan Village. Data were obtained through interviews, observations, and documentary studies. (1) The planning of reproductive health counseling in Srikamulyan Village is highly structured through three stages: (a) pre-counseling: preparation of materials, selection of facilitators, scheduling, socialization, preparation of venue and equipment; (b) counseling; (c) post-counseling: evaluation of results and follow-up. (2) The counseling implementation was successful with 43 active adolescent participants in three main sessions delivered by competent facilitators. (3) The results of the counseling reflect the success of the event with positive feedback from participants and facilitators, motivating participants, and enhancing interaction. Follow-up activities are needed, including ongoing activities and utilizing participant feedback for program improvement.